Influence of Fixed Orthodontic Treatment Duration on the Prevalence and Severity of Gingival Enlargement - Rajkanikar, Junima; Vaidya, Samriddhi; Piya, Anshu (Nepal Medical College Journal, 2024)
In patients undergoing fixed orthodontic therapy, favorable conditions for plaque stagnation as well as difficulty in performing usual oral hygiene measures have been associated with poorer periodontal health among orthodontic patients. So this study aims to assess the effect of the duration of fixed orthodontic treatment on presence of gingival enlargement in adolescents and young adults. This cross sectional descriptive study was conducted in the dental hospital of Nepal Medical College Teaching Hospital. Patients under fixed orthodontic therapy for at least 3 months were examined for the presence of gingival enlargement (GE). Demographic variables and the details of duration of the fixed orthodontic therapy was recorded along with presence of gingival enlargement and its grading. The oral hygiene habits like frequency of brushing, use of interdental cleaning aids were recorded along with plaque index. Gingival enlargement was present in 204 (63.7%) out of total 320 patients taken, among which 124 patients (38.8%) had gingival enlargement of score 1 and 80 (25.0%) patients had gingival enlargement of score 2. Gingival enlargement was observed in 101 (73.2%) in 20-30 years old patients which was more prevalent in this age group. Oral hygiene habits like frequency of brushing and use of interdental aids also seem to affect the occurrence of gingival enlargement in patients. Among those who were undergoing orthodontic therapy for more than 2 years, 48 (82.8%) had presence of gingival enlargement. Mean of plaque index was seen to be statistically associated with presence of gingival enlargement. Thus, this study showed that the duration of orthodontic treatment duration significantly influenced the occurrence of GE. Therefore, oral hygiene instructions and motivations should be reinforced for patients undergoing orthodontic treatment.